Predictors of success of trial of labor after cesarean section: A nested case–control study at public hospitals in Eastern Ethiopia - Maleda Tefera (SAGE Publishing, 2021)
Background: One of the primary reasons for an increase in cesarean sections is obstetricians’ uncertainty about labor trial safety following a previous cesarean section. The success rate of vaginal birth after cesarean section with a single cesarean scar is greater than 50%. However, to the best of our knowledge, there is a scarcity of information on the determinants of vaginal birth after cesarean delivery in the study area. As a result, the purpose of this study was to identify predictors of successful vaginal birth after cesarean delivery in public hospitals in Eastern Ethiopia. Methods: A nested case–control study design was used within a prospective follow-up study conducted from June to October 2020. A total of 220 women who tried vaginal birth after cesarean delivery was included, 110 cases and 110 controls. Cases were women with one previous cesarean section scar and successfully proceed with vaginal delivery. The controls were those with an earlier cesarean section scar and delivered by emergency cesarean section after trial of labor. A pre-tested structured questionnaire was used to gather the information. Multiple logistic regression is used to identify the determinants for the success of vaginal birth after cesarean section; odds ratio with its 95% CI are used to report the findings. Results: We found that living in rural areas (AOR = 2.28; 95% CI (1.85, 12.41)), having a current antenatal care follow-up (AOR = 3.20; 95% CI (1.15, 8.87)) and partograph monitoring of labor (AOR = 4.26; 95% CI (1.90, 9.57)) had a positive association with successful vaginal birth after cesarean section. In contrast, the presence of meconium-stained amniotic liquor (AOR = 0.10; 95% CI (0.01, 0.75)) and history of stillbirth (AOR = 0.07; 95% CI (0.02, 0.53)) reducing the chance of success of the trial. Conclusion: Past obstetric history, such as stillbirth, history of labor trial after primary cesarean section, and prior vaginal birth, were significant predictors for achieving vaginal birth after cesarean section. Antenatal care visit, and partograph follow-up were the current obstetric characteristics positively associated with the trial of labor.